Exploration of Kejawen in "Visit Central Java" version of KukuBima Ener-G advertisement - Rustono Farady Marta; Supina Supina; Erlina Fernando; William Yohanes; Ignatius Dwi Pulung Cahyanto (EduLite: Journal of English Education, Literature and Culture, 2022)
Developments in the era of globalization are in the world's spotlight, not only on differences in mindset but also on many aspects. One of them is the impact on the existence of culture in Indonesia. This fact drives companies in Indonesia to reintroduce Indonesian culture through advertising. An example is the Visit Central Java version of the KukuBima Ener-G advertisement explored in this study, intending to take an essential role in contributing to presenting local content that specifically raises the cultural side of Central Java. This study also aims at seeing the cultural values embedded in Javanese society, namely the Kejawen, which is implied in the KukuBima Ener-G advertisement. This study used a descriptive qualitative approach and data collection techniques using John Fiske's Semiotics Method to analyze more deeply the content of advertisements based on the Social Code Theory initiated by Edward T. Hall. This study explores deeper in terms of the strategy of cultural visual but still displays the brand image. The results of this study lead to the emergence of a number of Kejawen from the aspect of Low Context Culture and High Context Culture in each advertising scene.